Inquiries in psychiatric beyond - Mohamad Ismail, Maung Ko @ Hajee; Musa, Ramli; Au Bakar, Ahmad Zafri; Htwe, Ohnmar (Japan International Cultural Exchange Foundation & Japan Health Sciences University, 2013)
Introduction: There is tremendous development in scientific medicine; psychiatry is in need of such development for the diagnosis of functional and neurotic disorders. Certain pathological investigations are useful in assessing the medical cause of psychiatric presentations which constituted about 15 to 90%. Until a breakthrough in finding the cause of psychiatric illness, comprehensive data collection of patient's clinical picture and obtaining appropriate and detailed information are methods for getting reliable diagnoses. Objective: To highlight the role of investigations in Psychiatry until a break through in finding the aetiology of diagnosis. Method: Review the literature. Result: Psychosocial investigation is the only tool for assessing the diagnosis. It consists of history of the patient from a reliable source and getting information from family and friends. To diagnose disorders, doctor should acquire sufficient knowledgeabout disorders and must know their signs, symptoms, course and complications. Past and present history of the patient, family history, social history, medical history, mental state examination and physical examination are crucial to reach to the diagnoses and effective treatment. Furthermore, the biopsychosocial factors increasing the severity or reducing the severity is to be searched. Conclusion: At the present situations where there is no gold standard to diagnose psychiatric disorder as in other branch of medicine, we have to use a classification which is founded on symptomatology and not etiologically based. Therefore, in view of having diagnostic issues in psychiatry, physicians must be very thorough and systematic in approaching psychiatric cases so as to reach a proper diagnosis and immediate and effective treatment, which in turn will lead to improve the clinical outcome and quality of life of the patients. © 2013 Japan International Cultural Exchange Foundation & Japan Health Sciences University.